Property in some European Constitutions - Żbikowski, Wawrzyniec (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The aim of the study is to analyse the notion of property in the selected European countries' constitutions. The author present the constitution of Poland, Russia, Germany and France and confront with the construction of the right to property in the European Convention on Human Rights.